Three Modes of Valuation Practices in Art Games - Michael Hutter (Valuation Studies, 2021)
Several suggestions on distinguishing between “modes” of valuation practices are found in the literature. In this contribution, valuation practices are moves in a kind of social play that generates its own kind of value. Valuation in the Arts is chosen as an empirical example. Following the model, the Arts are interpreted as a set of games with the same kind of value code, in which artists and producers create performances for engaged and curious spectators. The four kinds of players engage in valuations of objects and other players in their respective games. The broad range of observations in art games demonstrates that valuation is practiced in three modes: attribution, assessment and payment. While practices of attribution and assessment generate and stabilize art-specific value accumulation, paying practices link the attributed and assessed values to the monetary valuation in games of commercial play. The distinctions of valuation practices employed by three recent authors are set into relation to the suggested modes.
Keywords: 300; valuation; consecration; evaluation; art games; orders of value